Endovascular Versus Surgical Revascularization for the Management of Chronic Mesenteric Ischemia. (January 2015) - Saedon, Mahmud; Saratzis, Athanasios; Karim, Ahmed; Goodyear, Steve
Background: Chronic mesenteric ischemia (CMI) can be treated with surgical revascularization (SR) or endovascular revascularization (ER). Materials and Methods: Systematic review of 12 studies comparing ER and SR in CMI. Primary end point was perioperative (30 days) survival. A secondary composite end point consisted of perioperative mortality, nonfatal cardiac events, nonfatal stroke, and nonfatal bowel ischemia. Further end points included late survival, primary patency, and symptom improvement. Results: The cumulative odds ratio (OR) for perioperative mortality was 0.78 (95% confidence interval [CI]: 0.40-1.50, P = .45) and 0.56 (95% CI: 0.28-1.11, P = .10) for the composite end point. The cumulative OR for survival after the 30th day was 0.83 (95% CI: 0.47-1.46), P = .51. Late primary patency was reported in 8 studies, with a cumulative OR of 3.57 (95% CI: 1.83-6.97, P = .0002)—favoring SR. Conclusion: In the first meta-analysis to compare ER and SR in CMI, there were no differences in mortality and morbidity. Patency rates were better following SR.